Physical self-efficacy in women`s artistic gymnastic between recreational and competitive level - Gomez Paloma, F.; Rio, L.; D`Anna, C. (Journal of Human Sport & Exercise, 2014)
In Bandura`s theory (1997, 2001), self-efficacy is the cognitive mechanism that mediates information on personal capacities to successfully execute necessary courses of action in a specific domain. It is theorized that self-efficacy belief influences motivation, affect and behaviour. Self-efficacy regarding motor activities has been widely investigated (Feltz, 1992) and represents a frame of reference to explain links between cognitive processes and physical performance (Colella & Morano, 2008). The purpose of the study was to verify the difference in physical self-efficacy (perceived) between gymnasts practicing sports at recreational level and gymnasts, however, which train at a competitive level. The Perceived Physical Ability Scale for Children by Colella (2008) was presented to a sample of 58 gymnasts, 29 practicing sports at recreational level and 29 practicing sports at competitive level in random selection, ranging in age from 8 to 10 years old. The items of the PPASC are: speed, ability, strength, rapidity, self-confidence and tiredness. They are structured in response scales having a 1- to 4-point format. Observing the results of the descriptive statistics in the whole sample it is obvious how the perceived physical abilities are very high in all items. The artistic gymnastic is a sport in which these aspects of physical abilities are trained specifically. The children say that they run fast (77 %), they are able to do difficult exercises (77%), their muscles are strong (68%) and move rapidly (71%). Slightly lower values ??are those related to self-confidence, the 48% say that they feel sure when they move but the 32% say that they feel somewhat insure when they move, and the value of energy, 50% say I don`t feel tired when I move, but the 25% say that they feel tired. The difference between the values of the two levels of gymnastic report in the competitive groups is higher in physical self-efficacy in all items than in the recreational group. These data could suggest that the quantity of the trainings and, at the same time, the improvement of the quality of the performance increases the Perceived Physical Ability. The results of the test is particularly high and considering it globally, confirms that, in any case, the physical activities, even if only practiced as recreational activity, produces positive effects on the Perceived Physical Ability.